PENGARUH KARAKTERISTIK PASIEN TERHADAP INDEKS KEPUASAN MASYARAKAT TENTANG PELAYANAN RAWAT JALAN PUSKESMAS BANYUMAS - Kurniawan, Arif; Intiasari, Arih Diyaning (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2012)
ABSTRACT 169   Level of satisfaction of community service to public health  centers need to meet the standards of public service minister by decree in 2004. Based on the above background research done on the influence of patient characteristics on the satisfaction index of ambulatory service in Banyumas public health center. This study aims to analyze the public about the service satisfaction index  of ambulatory service in Banyumas public health center and the influence  factors on the satisfaction index. This study is an observational study with survey research methods. The approach of this study using cross-sectional approach. The study population was all households in Banyumas public health center. The research sample consists of 150 people, with accidental sampling method. Retrieval research data using a questionnaire instrument. Analysis of research data using univariate analysis, bivariate analysis, and multivariate analysis. The research was conducted in Banyumas public health center. Results showed that most people (51.3%) satisfied with the service ambulatory, and 48.7% of the public are not satisfied with the service ambulatory in Banyumas public health center. There was no association between age, occupation, gender, and status of financing of patient satisfaction with the level of ambulatory service in Banyumas public health center. There is a relationship between education and marital status of patients with levels of satisfaction ambulatory service in Banyumas public health center. There are influences together education and marital status of patients with level of satisfaction ambulatory service in Banyumas public health center. Proposed study is Banyumas public health center to immediately improve patient care aspects of the course mainly discipline officers in providing service. Kesmasindo. Volume 5( 2)  Juli  2012,  hlm. 169- 179 Keywords: patient characteristics, community satisfaction, ambulatory service